The Separation of Railway Costs between Freight and Passengers - Parmelee, Julius H. (Quarterly Journal of Economics, 1920)
Three aspects of the problem, 346. — Separation of costs between freight and passengers, 348. — Cost separation required by Interstate Commerce Commission in 1888, abandoned in 1902, 349. — Tentative classification in 1915 and discussion thereon, 353. — Partial separation again required in 1916, but suspended on outbreak of war, 354. — A system of separation again established, going into effect January 1, 1920, 355. — Concluding remarks on the general problem, 360.